Effects of long-term organic fertilizer and straw on soil quality and crop yield in a rapeseed–maize rotation system - Xiaoqin Tian; Tingting Yang; Zhuo Li; Yonghong Liu (PLoS ONE, 2025)
This study aimed to pursue more sustainable agriculture in a new rapeseed–maize rotation system. We assessed the effects of organic fertilizer and straw on soil quality and crop yield through a 15-year field experiment: mainly applied organic fertilizer (MM); mainly applied inorganic fertilizer with straw (MCS); mainly applied inorganic fertilizer (MC); applied only inorganic fertilizer with straw (CS); and applied only inorganic fertilizer (C) as a control. Compared to the C treatment, crop yields, soil organic carbon (SOC), available nitrogen (AN), phosphorus (AP), potassium (AK), soil porosity (SP), field capacity (FC), and 0.250–2.000 mm large aggregates in soil water-stable aggregates (WA0.250-2.000) were significantly (P<0.05) increased by organic fertilization treatments (MCS, MC, and MM); and soil bulk density (SBD) and WA<0.053 were significantly decreased. Similarly, straw addition (CS and MCS) treatments also had significant effects on soil nutrients, structure, and yield, compared to the C and MC treatments, respectively. However, compared to the MC treatment, applying more organic fertilizers (MM) had no significant effect. The highest nutrient comprehensive evaluation value (NCEV), SP, FC, MA>2.000, WA0.053–0.250, and crop yields were observed in the MCS treatment. Compared to C treatment, rapeseed and maize yield significantly increased by 36.0% and 11.8% in response to MCS treatment, respectively. Pearson correlations showed that total nitrogen (TN), total potassium (TK), AK, SBD, and WA<0.053 were the strongest correlates of crop yields, followed by SOC, FC, WA>2, and WA0.250–2.000. This suggests that MCS was the best fertilization method to increase crop yields by improving SOC, AK, FC, and WA>0.250, and reducing SBD and WA<0.053.